Corrigendum to “Susceptibility of Spodoptera frugiperda to novel insecticides and detection of known target-site mutations following invasion of Taiwan” [J. Asia-Pac. Entomol. 29(3) (2026)102584] - Hung-Ming Chao; Wen-Jer Wu; Li Lin; Hurng-Yi Wang; Ju-Chun Hsu (Journal of Asia-Pacific Entomology, 2026)

Susceptibility of Spodoptera frugiperda to novel insecticides and detection of known target-site mutations following invasion of Taiwan - Hung-Ming Chao; Wen-Jer Wu; Li Lin; Hurng-Yi Wang; Ju-Chun Hsu (Journal of Asia-Pacific Entomology, 2026)

Inhibitory effects of fruit powders on heterocyclic amine formation in charcoal-grilled pork: A comparative study of application methods and development of a functional barbecue sauce spray - Mei-Ling Li; Yu-Shun Lin; Pei-Yu Wu; Ling-Hsuan Chang; Shang-Ming Huang; Kuo-Chiang Hsu (Food Research International, 2026)

Acidified freshwater disrupts skeletal mineralization and bone remodeling gene expression in zebrafish (Danio rerio) larvae - Chia-Hao Lin; Jun-Yi Wang; Ming-Fan Li; Hsuan-Yi Hsu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

A food-derived octapeptide SRGQIEEL from yellow field pea protein hydrolysates inhibits xanthine oxidase via a tunnel-occlusion-like mechanism - Mei-Ling Li; Cheng-Hong Hsieh; Pei-Yu Wu; Shang-Ming Huang; Chung-Yu Tang; Yu-Shun Lin; Kuo-Chiang Hsu (Food Bioscience, 2026)

Phylogeny and Taxonomy of the Coral Reef Maidenhair Fern Adiantum capillus‐veneris subsp. lanyuanum (Pteridaceae) in East Asia - Zhi‐Xiang Chang; Tian‐Chuan Hsu; Xinping Qi; Ching Ming Hsieh; Atsushi Ebihara; Yi‐Han Chang; Yao‐Moan Huang; Li‐Yaung Kuo (New Zealand Journal of Botany, 2026)
Adiantum capillus‐veneris is a species with a worldwide distribution, exhibiting considerable morphological variation, with several infraspecific names applied. Among these infraspecific taxa, A. capillus‐veneris subspecies lanyuanum can be easily distinguished from typical A. capillus‐veneris by its small and 1‐pinnate fronds. This form has been recorded from a few insular populations in Taiwan and Japan, typically inhabiting moist and shaded coral reef cliffs. A chloroplast DNA phylogeny further demonstrates that collections of subsp. lanyuanum across different populations formed a well‐supported clade, and also provides evidence of its genetic distinctiveness and differentiation. Further examination of herbarium specimens and field observations found that, in addition to frond morphology, the rhizome scale differences are also useful for distinguishing the two taxa. As a consequence, A. capillus‐veneris subsp. lanyuanum comb. nov. is proposed as the appropriate taxonomic designation of this taxa and a neotype is designated.

Prenatal and postpartum residential greenness and behavioral development in early Childhood: Findings from a birth cohort - Wen-Chi Chao; Ming-Lun Zou; Chih-Da Wu; Jian-Pei Huang; Heng-Kien Au; Chen-Li Lin; Shih-Peng Mao; Hsing-Jasmine Chao; Ling-Chu Chien; Hsueh-Wen Hsu; Pilyoung Kim; Yi-Hua Chen (Environmental Research, 2026)

Correction: Severe enterovirus A71 pathogenesis and immune responses in human nucleolin transgenic mice - Nien-En Hsiao; Ya-Fang Wang; Yi-Chen Lin; Wei-Ting Chou; Li-Jin Hsu; Shih-Min Wang; Jen-Ren Wang; Ming-Derg Lai; Shun-Hua Chen; Chuan-Fa Chang (Medical Microbiology and Immunology, 2025)

Severe enterovirus A71 pathogenesis and immune responses in human nucleolin transgenic mice - Nien-En Hsiao; Ya-Fang Wang; Yi-Chen Lin; Wei-Ting Chou; Li-Jin Hsu; Shih-Min Wang; Jen-Ren Wang; Ming-Derg Lai; Shun-Hua Chen; Chuan-Fa Chang (Medical Microbiology and Immunology, 2025)

Neuroprotective Effects of Glucosamine in Huntington’s Disease Through NLRP3 Inflammasome Inhibition - Lichieh Julie Chu; Yi-ting Hsu; Yu Aoh; Chih-Yuan Cheng; Hui-Hsuan Wang; Ming-Tse Wu; Hao-Hsuan Li; Xiu-Yuan Lai; Kuo-Feng Hua; Chiung-Mei Chen; Tz-Chuen Ju (Journal of Neuroimmune Pharmacology, 2025)

Precision monitoring of rice nitrogen fertilizer levels based on machine learning and UAV multispectral imagery - Ming-Der Yang; Yu-Chun Hsu; Yi-Hsuan Chen; Chin-Ying Yang; Kai-Yun Li (Computers and Electronics in Agriculture, 2025)

Reducing melamine exposure and oxidative stress markers in melamine-exposed workers: A pragmatic intervention study - Chia-Fang Wu; Chih-Hong Pan; Yu-Ming Hsu; Chiung-Yu Peng; Ching-Mei Cheng; Sih-Syuan Li; Chien-Ping Huang; Ming-Tsang Wu (Journal of Hazardous Materials, 2025)

Polycyclic aromatic hydrocarbon aggravates high-fat diet-induced metabolic dysfunction-associated steatotic liver disease through disturbing hepatocyte sphingolipid metabolism - Hui-Ru Kuo; Yu-Fen Chung; Li-Ting Wang; Chih-Wen Wang; Shih-Hsien Hsu; Li-Chen Chen; Ming-Hong Lin; Shau-Ku Huang; Kwei-Yan Liu (Environmental Pollution, 2025)

Development and Evaluation of a Dual-Mode Cold Atmospheric Plasma System for Stage-Specific Wound Healing Applications - Ching-Yuan Lin; Dong-Jin Li; Yu-Shen Chen; Chia-Wei Hsu; Mohd Yaqub Khan; Ming-Chen Wang (Journal of Medical and Biological Engineering, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Early postnatal and concurrent exposure to metals and neurobehavioral outcomes at 5 years: Associations with individual environmental exposures and mixtures - Sui-Ling Liao; Shen-Hao Lai; Yuan-Ting Hsu; Li-Chen Chen; Ming-Han Tsai; Man-Chin Hua; Tsung-Chieh Yao; Kuan-Wen Su; Kuo-Wei Yeh; Chih-Yung Chiu; Shau-Ku Huang; Jing-Long Huang (NeuroToxicology, 2024)

Capnesterones A and B, new steroids isolated from the soft coral Capnella imbricata - Ting-Yu Cheng; Chia-Jung Yang; Po-Jen Chen; Yu-Li Chen; Bo-Rong Peng; Te-An Kung; Zhi-Hong Wen; Kuei-Hung Lai; Hsu-Ming Chung (Phytochemistry Letters, 2024)

Testing the moderated mediation effect of recreation safety climate on the interrelationship of serious leisure, recreation involvement, and flow experience - Tien-Ming Cheng; Ching-Yi Hsu; Shan-Ni Li (Journal of Outdoor Recreation and Tourism, 2024)

Tannic Acid Impedes the Proliferation of Bladder Cancer Cells by Elevating Mitochondrial Pathways of Apoptosis - Chi-Cheng Li; Bruce Chi-Kang Tsai; Selvaraj Annseles Rajula; Chiung-Hung Hsu; Ming-Cheng Chen; Chia-Hua Kuo; Chung-Min Yeh; Dennis Jine-Yuan Hsieh; Wei-Wen Kuo; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2024)

Systematics and evolutionary dynamics of insect-fern interactions in the specialized fern-spore feeding Cuprininae (Lepidoptera, Stathmopodidae) - Zong-Yu Shen; Takeshi Terada; Jean-François Landry; Robert J.B. Hoare; Li-Yaung Kuo; Ming-Hsun Chou; Yu-Feng Hsu; Jen-Pan Huang (Molecular Phylogenetics and Evolution, 2024)

Quantifying the effects of viral load on multistate COVID-19 infection and the progression of the Alpha and Omicron VOCs: a Bayesian competing Markov exponential regression model - Yen-Po Yeh; Amy Ming-Fang Yen; Ting-Yu Lin; Chen-Yang Hsu; Sam Li-Sheng Chen; Tony Hsiu-Hsi Chen (Stochastic Environmental Research and Risk Assessment, 2024)

Flash drought evaluation using evaporative stress and evaporative demand drought indices: a case study from Awash River Basin (ARB), Ethiopia - Yitea Seneshaw Getahun; Ming-Hsu Li (Theoretical and Applied Climatology, 2024)
Drought is one of the most devastating phenomena that affect the livelihood of most communities in Ethiopia as they have low adaptive capacity. Recent advancements in remote sensing and drought investigations have made it possible to identify a new type of flash drought that has rapid intensification with a short duration (i.e., less than 1 month unlike conventional droughts). This study intends to identify flash drought in the Awash River Basin (ARB) based on Moderate Resolution Imaging Spectroradiometer (MODIS) data of actual evapotranspiration and potential evapotranspiration using Evaporative Demand Drought Index (EDDI) and Evaporative Stress Index (ESI) indices. The flash drought result exhibited that agricultural lands, grasslands, vegetation areas, and irrigational croplands along the river were vulnerable to flash drought in the ARB. Using ESI, the area of ARB that experienced flash drought in 2002, 2008, 2009, 2012, and 2015 were 23%, 40%, 20%, 40%, and 24%, respectively. These intense flash drought areas can be used as drought monitoring sites. The flash drought extent of EDDI is more compared to ESI because of ESI’s dependency on vegetation coverages and soil moisture. The lowland downstream part of the ARB is highly prone to flash drought, particularly in the major rainy season (MRS) and the last two months of the minor rainy season (mRS). EDDI can discern the onset of flash drought better compared to ESI, but both can be used as a drought early warning mechanisms to minimize agricultural losses and drought-associated risks in the basin.

Exploration of the Catalytic Cycle Dynamics of Vigna Radiata H+–Translocating Pyrophosphatases Through Hydrogen–Deuterium Exchange Mass Spectrometry - Li-Kun Huang; Yi-Cyuan Huang; Pin-Chuan Chen; Ching-Hung Lee; Shih-Ming Lin; Yuan-Hao Howard Hsu; Rong-Long Pan (The Journal of Membrane Biology, 2023)

Simultaneous electrochemical determination of benzenediol compounds in environmental samples using nano architectures of hydrogen ammonium zinc molybdate layered double hydroxides integrated with carbon black modified electrode - Chelladurai Karuppiah; Sivakumar Musuvadhi Babulal; Shen-Ming Chen; Selvakumar Palanisamy; Li-Fan Hsu; Chun-Chen Yang; Matteo Chiesa (Journal of Water Process Engineering, 2023)

Recombinant Streptomyces netropsis transglutaminase expressed in Komagataella phaffii (Pichia pastoris) and applied in plant-based chicken nugget - Ming-Li Shen; Jhih-Ying Ciou; Lu-Sheng Hsieh; Chuan-Liang Hsu (World Journal of Microbiology and Biotechnology, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Anti-inflammatory cembrane-based diterpenoids isolated from the octocoral Sinularia querciformis - Te-An Kung; Lo-Yun Chen; Chia-Ying Li; Bo-Rong Peng; Tsong-Long Hwang; Ping-Jyun Sung; Kuei-Hung Lai; Hsu-Ming Chung (Phytochemistry Letters, 2023)

Modelling chloroform in indoor swimming pool air and water: the influences of internal air circulation and occupants - Hui-Tsung Hsu; Ming-Jen Chen; Kuang-Chung Tsai; Li-Jen Huang; Ching-Ho Lin; Chin-Hsing Lai; Li-Hsin Cheng (Environmental Science and Pollution Research, 2023)

Multiple drought indices and their teleconnections with ENSO in various spatiotemporal scales over the Mekong River Basin - Thi-Thu-Ha Nguyen; Ming-Hsu Li; Tue Minh Vu; Pei-Yuan Chen (Science of The Total Environment, 2023)

A new approach to modeling pre-symptomatic incidence and transmission time of imported COVID-19 cases evolving with SARS-CoV-2 variants - Sam Li-Sheng Chen; Grace Hsiao-Hsuan Jen; Chen-Yang Hsu; Amy Ming-Fang Yen; Chao-Chih Lai; Yen-Po Yeh; Tony Hsiu-Hsi Chen (Stochastic Environmental Research and Risk Assessment, 2023)

Tannic acid attenuate AKT phosphorylation to inhibit UMUC3 bladder cancer cell proliferation - Ming-Cheng Chen; Selvaraj Annseles Rajula; V. Bharath Kumar; Chiung-Hung Hsu; Cecilia Hsuan Day; Ray-Jade Chen; Tso-Fu Wang; Vijaya Padma Viswanadha; Chi-Cheng Li; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2022)

The Effect of Co-Exposure to Glyphosate, Cadmium, and Arsenic on Chronic Kidney Disease - Junne-Ming Sung; Wei-Hsiang Chang; Kuan-Hung Liu; Chung Yu Chen; Trias Mahmudiono; Wan-Ru Wang; Ho-Chi Hsu; Zhen-Yi Li; Hsiu-Ling Chen (Exposure and Health, 2022)

Insertion Speed Affects the Initial Stability of Dental Implants - Yuan-Yang Hsu; Ming-Tzu Tsai; Heng-Li Huang; Lih-Jyh Fuh; Jui-Ting Hsu (Journal of Medical and Biological Engineering, 2022)
Purpose This study investigated the effects of insertion speed of dental implants on their stability. Methods Dental implants were inserted at speeds of 4, 10, 20, and 30 rpm, respectively, into artificial bones of two different bone qualities; namely, good bone (GB) and poor bone (PB). Therefore, the four insertion speeds and two bone qualities totaled eight groups, with five specimens per group. During the insertion process, the maximum insertion torque value (ITV) was measured, along with two stability parameters: periotest value (PTV) and initial stability quotient (ISQ). Results Dental implants in the GB group exhibited better stability than those in the PB group (p < 0.001). Significant differences in ITVs were observed among the four insertion speeds in both the GB and PB groups (p = 0.004 and p = 0.034, respectively). In general, the higher the insertion speed, the lower the ITV; in particular, the ITVs for implants inserted at 4 rpm were higher than those measured at 20 and 30 rpm (p = 0.008). However, regardless of the bone quality, the PTVs did not differ significantly among the four insertion speeds (p = 0.066). In both the GB and PB groups, the ISQs differed significantly differences among the four insertion speeds (p = 0.016 and p = 0.004, respectively). Conclusion The stability parameters measured for dental implants in the GB group were all higher than those measured in the PB group. In general, a higher insertion speed resulted in a lower ITV value. The PTV did not differ significantly, while the ISQ differed significantly among the four insertion speeds.

Altered Connectedness of the Brain Chronnectome During the Progression to Alzheimer’s Disease - Maryam Ghanbari; Zhen Zhou; Li-Ming Hsu; Ying Han; Yu Sun; Pew-Thian Yap; Han Zhang; Dinggang Shen (Neuroinformatics, 2022)

Spontaneous thought-related network connectivity predicts sertraline effect on major depressive disorder - Li-Ming Hsu; Timothy Joseph Lane; Changwei W. Wu; Chien-Yuan Lin; Chi-Bin Yeh; Hung-Wen Kao; Ching-Po Lin (Brain Imaging and Behavior, 2021)

Enhancement of IUdR Radiosensitization in Cancer Therapy by Low-Energy Transmission X Ray Irradiation - Chien-Chih Ke; Jia-Je Li; Hsueh-Peng Wu; Wen-Wang Kuo; Yi-An Chen; Cheng-Hsiu Lu; Hsin-Ell Wang; Shih-Ming Hsu; Ya-Ju Hsieh; Ren-Shyan Liu (Journal of Medical and Biological Engineering, 2021)

Shall We Profile the Measuring Postures and Amounts of Stress? A Novel Stress-View Evaluation System for Quantifying Trapeziometacarpal Joint Laxity - Li-Chieh Kuo; Po-Hao Hsu; Chien-Kuo Wang; I-Ming Jou; Chieh-Hsian Hsu; Kai-Nan An (Journal of Medical and Biological Engineering, 2018)

Goatpoxvirus ATPase activity is increased by dsDNA and decreased by zinc ion - Ming-Liang Lee; Wei-Li Hsu; Chi-Young Wang; Hui-Yu Chen; Fong-Yuan Lin; Ming-Huang Chang; Hong-You Chang; Min-Liang Wong; Kun-Wei Chan (Virus Genes, 2016)

Effects of rice straw ash amendment on Cd solubility and distribution in a contaminated paddy soil under submergence - Sheng-Huie Hsu; Shan-Li Wang; Jang-Hung Huang; Shiuh-Tsuen Huang; Ming K. Wang (Paddy and Water Environment, 2015)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

Calreticulin Mediates Nerve Growth Factor-Induced Neuronal Differentiation - Yu-Yin Shih; Akira Nakagawara; Hsinyu Lee; Hsueh-Fen Juan; Yung-Ming Jeng; Dong-Tsamn Lin; Yung-Li Yang; Yeou-Guang Tsay; Min-Chuan Huang; Chien-Yuan Pan; Wen-Ming Hsu; Yung-Feng Liao (Journal of Molecular Neuroscience, 2012)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Editing of accD and ndhF chloroplast transcripts is partially affected in the Arabidopsis vanilla cream1 mutant - Ching-Chih Tseng; Tzu-Ying Sung; Yi-Chiou Li; Shih-Jui Hsu; Chien-Li Lin; Ming-Hsiun Hsieh (Plant Molecular Biology, 2010)

Secular trend of genome types of respiratory adenovirus type 3 during 1983–2005: a study from Taiwan - Yung-Cheng Lin; Kuei-Hsiang Lin; Guan-Ming Ke; Min-Sheng Lee; Pei-Chin Lin; Hsin-Fu Liu; Li-Ching Hsu; Po-Liang Lu (Archives of Virology, 2010)

Numerical modeling of coupled fluid flow and thermal and reactive biogeochemical transport in porous and fractured media - Gour-Tsyh Yeh; Yilin Fang; Fan Zhang; Jiangtao Sun; Yuan Li; Ming-Hsu Li; Malcolm D. Siegel (Computational Geosciences, 2010)

Interval number fuzzy linear programming for climate change impact assessments of reservoir active storage - Ching-Pin Tung; Nien-Ming Hong; Ming-hsu Li (Paddy and Water Environment, 2009)

Assessing the impact of climate change on the land hydrology in Taiwan - Ming-Hsu Li; Waiting Tien; Ching-Pin Tung (Paddy and Water Environment, 2009)

Complex genomic organization of Indian muntjac centromeric DNA - Ya-Ming Cheng; Tzai-Shiuan Li; Lie-Jiau Hsieh; Pei-Ching Hsu; Yueh-Chun Li; Chyi-Chyang Lin (Chromosome Research, 2009)

Reduction of anion exchanger 2 expression induces apoptosis of human hepatocellular carcinoma cells - Jin-Ming Hwang; Shao-Hsuan Kao; Yi-Hsien Hsieh; Kuen-Lin Li; Pei-Hsi Wang; Li-Song Hsu; Jer-Yuh Liu (Molecular and Cellular Biochemistry, 2009)

Distributed Flood Simulations with Coupling Gauge Observations and Radar-rainfall Estimates - Dong-Sin Shih; Ming-Hsu Li; Ray-Shyan Wu (Water Resources Management, 2008)

An Assessment of Structural Measures for Flood-prone Lowlands with High Population Density along the Keelung River in Taiwan - Lung-Sheng Hsieh; Ming-Hsi Hsu; Ming-Hsu Li (Natural Hazards, 2006)

Inundation Potentials Analysis for Tsao-Ling Landslide Lake Formed by Chi-Chi Earthquake in Taiwan - Ming-Hsu Li; Ming-Hsi Hsu; Lung-Sheng Hsieh; Wei-Hsien Teng (Natural Hazards, 2002)